An assessment of the van-for-hire as a local public transport mode in Bohol - Doroy, Nelson B. (2005)
Alternative public transportation modes, often called as paratransits, are widely being used in the Philippines. The paratransits in the country are usually outside of government public transport regulations and do not belong to any of the existing standard classification of public conveyances. Yet, the trend of these alternative public transportservices has been steadily increasing in the provinces such as the van-for-hire services in Bohol. Hence, there is a need to determine the role of these services in the overall public transport system of a local area. The objective of this research is to ascertain the present role of the van-for-hire as a local public transport mode in Bohol. This study also seeks to characterize the emergence and existence of the van-for-hire as a public transport mode in Bohol. Ultimately, this paper aims to make recommendations on regulatory measures regarding the vans-for-hire as a local public transport mode in Bohol. Through the use of several research tools such as passenger travel behavior survey, driver profile survey, stated preferences survey, statistical test and engineering economic analysis, the study was able to show that a new type of service emerged and continues to exist as a distinct shared-type public transport mode offering lower travel time than the bus service. Most of this demand comes from the middle-income passengers who can afford a higher travel cost for a lower travel time. And since there is a current demand for the van-for-hire operating as a commuter service, this shared-type of service becomes viable investment opportunity for the operators and a good source of livelihood for the drivers. However, this shared-type of service can not be considered as sustainable primarily because it is outside of any regulatory environment. It is thus suggested that a new public conveyance classification be created to accommodate all the vans that are operating as a commuter service similar to the bus service. With the availability of a wide array of data for the vans-for hire in Bohol, future research can be suggested into the direction of modeling the mode choice behavior of the van-for-hire and bus passengers. Similar studies can also be conducted on other provinces of the region to address the issue on a regional scale.